PEMIDANAAN PELAKU TINDAK PIDANA ANAK: ANTARA PERLINDUNGAN DAN PENGHUKUMAN - Ade Rhomana; Rizky Yohanes; Josua Parulian Manurung; Fiqih Arif Fadhillah; Devan Ariza Putra; Sufiarina (The Juris, 2025)
This study aims to analyze the punishment of child criminals in the Indonesian juvenile justice system and to assess the balance between child protection and punishment as a form of criminal accountability. The research method used is normative juridical research with analytical descriptive specifications, which focuses on the study of legal norms, legal principles, and the concept of child punishment in legislation. The data used is secondary data consisting of primary legal materials and secondary legal materials obtained through literature studies. The data is analyzed using qualitative analysis techniques, namely by interpreting and explaining the applicable legal provisions with the practice of child punishment. The results of the study indicate that although the juvenile justice system in Indonesia has normatively placed the protection and best interests of children as the main principle, in practice, punishment still tends to be oriented towards punishment through imprisonment. This approach has the potential to have a negative impact on child development and hinder the process of rehabilitation and social reintegration. This study concludes that the punishment of child criminal offenses should be placed as a last resort and directed towards a more proportional, humanistic approach, oriented towards training and recovery without ignoring the interests of justice for victims and society.